Wash-free non-spectroscopic optical immunoassay by controlling retroreflective microparticle movement in a microfluidic chip. Issue 23 (25th October 2019) - Kim, Ka Ram; Chun, Hyeong Jin; Lee, Kyung Won; Jeong, Kwan Young; Kim, Jae-Ho; Yoon, Hyun C.
Abstract : A wash-free nonspectroscopic optical immunoassay system by controlling retroreflective Janus microparticles movement in a microfluidic chip was developed to minimize random errors under the point-of-care testing environment. Abstract : Here, we proposed a retroreflective optical immunoassay platform by introducing the intrinsic sedimentation characteristics of a micro-retroreflector, namely retroreflective Janus particles (RJPs), wherein the sediment-based passive movement of RJPs minimised the random errors due to human involvement and resulted in a simple procedure that does not require the washing step, to follow the concept of point-of-care testing. The transparent sensing interface and the sedimentation property of RJPs were combined to develop a practical retroreflective immunoassay platform. For the sensing surface, transparent silanized poly(methyl methacrylate) was applied to the inverted focusing method. In the retroreflection phenomenon, as the incident light returns to its source by the retroreflector, efficient design of the retroreflective optical path between the light source and retroreflector can be crucial in signal registration. While preparing the RJP-bound transparent substrate on the microfluidic channel, the signal could be achieved more efficiently by directly focusing on the sensing interface, and not via the fluidic channels. To integrate this to build an immunoassay protocol, the sedimentation property of RJPs was employed for microfluidic chip inversion-based particle movement control, which was utilised for both luring and separating RJPs on the sensing surface, resulting in a wash-free immunoassay without any human involvement. To ensure accurate analysis, a time-lapse imaging-based image processing was conducted to eliminate the non-specific signals. To validate the applicability of the proposed immunoassay platform, quantification of acute cardiac infarction marker creatine kinase-MB was performed.